Severe Neonatal Pertussis Treated by Leukodepletion and Early Extra Corporeal Membrane Oxygenation. Issue 9 (September 2015) - Assy, Jana; Séguéla, Pierre-Emmanuel; Guillet, Elodie; Mauriat, Philippe
Abstract : We report the case of a 17-day-old infant with severe pertussis for whom the early initiation of veno-arterial extra corporeal membrane oxygenation and leukodepletion strategies (exchange transfusion and leukofiltration) allowed to reduce leukocytosis and pulmonary hypertension, thus leading to survival. These invasive techniques can be considered when severe pulmonary hypertension complicates hyperleukocytosis in neonates. Abstract : Supplemental Digital Content is available in the text.